Consumer Attitude Towards the Cell Phone: A study on Young Generations of Chittagong Metropolitan City, Bangladesh - Chowdhury, Mrs. Tanzina; Rahman, Mohammad Toufiqur (Asian Business Review, 2013)
Due to increased competition, locally as well as internationally, organizations need a distinguishing element that will keep consumers identifying and buying their product. This study employs to analyze the relationship between demographic variables on the brand preference and is identifying the attributes that affect the choice behavior of mobile hand set as well as why the young consumers give special emphasis to some particular factors in Chittagong metropolitan city. From the study we see that though both male and female respondents now using Nokia (57.92%) hand set but about 50.61% of male & 59.85% of female respondent choices Samsung mobile set as their most favorite brand to next purchase because of android operating system. We also see that both newspaper (39.82%) and television (36.18%) has a great influence over the respondents to choose the above mentioned mobile hand set as their favorite brand. About 67.16 % of respondents are willing to spend money more than Tk. 10,000 to get the test of latest features provided by the various mobile set companies. JEL Classification Code: E31